Plasma sodium and potassium levels in Gir and Jaffarabadi breeds: Effect of age, sex and lactation (Indian Journal of Animal Production and Management, 2018)
A study was conducted on Gir and Jaffarabadi breeds of both sexes to determine the effect of age, sex and  lactation on plasma sodium and potassium levels (mEq/L). Age exerted a significant (P < 0.05) effect on  plasma potassium levels only in Jaffarabadi males. In Gir cows, lactation influenced the plasma potassium  levels significantly (P < 0.05). The plasma levels of potassium between males, females, at 1 and 2 m of  lactation, non lactating females of Gir and Jaffarabadi breeds varied significantly (P < 0.05). Moreover, low  level of both plasma sodium and potassium was observed at all ages and lactation in Jaffarabadi buffaloes  as compared to Gir cattle. Further this could be used as a reference point for future research in these breeds.